PENGARUH PENGEMBANGAN SISTEM KERJA DAN KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN KARYAWAN PADA PT. RADITYA DEWATA PERKASA - Putu Wiwin Aprilia Dewi; Ni Nyoman Suryani; I Nyoman Resa Adhika (EMAS, 2021)
Low employee productivity is one symptom that can damage conditions in a company. At PT. Raditya Dewata Perkasa has decreased employee productivity due to a lack of understanding and ability of employees to apply the development of work systems. This study aims to determine the effect of developing work systems and work ability partially and simultaneously on employee productivity. The location of this research at PT. Raditya Dewata Perkasa. The population uses employees of PT. Raditya Dewata Perkasa and a sample of 40 employees. The data analysis technique used the validity test, reliability test, classical assumption test, multiple linear regression analysis, determination coefficient test, F test and t test. From the research results, the results obtained: (1) the development of work systems has a significant positive effect on employee productivity, where the regression coefficient value is 0.197 and a significance value is 0.036. (2) work ability has a significant positive effect on employee productivity, where the regression coefficient value is 0.369 and a significance value is 0.007. (3) simultaneous development of work systems, and have a significant effect on employee productivity, where a significance value of 0.000 is obtained. The amount of influence of the independent variables on employee productivity is 55.4%. The suggestions that can be given by researchers are PT. Raditya Dewata Perkasa should provide training to employees, guide employees and provide motivation and adequate work facilities.